Digitalization during the era of COVID-19: An analysis of the psychophysiological strain of university students - Babieva, Nigina S.; Romanova, Anzhela V.; Reznichenko, Sergey A.; Kosykh, Oksana I.; Kosolapova, Natalia V.; Vlasenko, Larisa V.; Krasheninnikova, Ekaterina I. (Frontiers in Education, 2022)
The pandemic has created a push for changes in education and technology that are driving progress in all areas of instruction. This impetus is forcing all stakeholders to address the transformation of traditional education into online education. This change in the education system requires students and teachers to train new competencies, knowledge, skills, and abilities. In this context, this paper aimed to determine the psychophysiological strain of university students in relation to distance learning during the pandemic COVID-19. For this aim, quantitative data collection was conducted in this research. The results indicated that the distance learning format increased neuropsychic strain, decreased mood, activity, and wellbeing, and increased situational anxiety in college students. Based on the obtained results, social pedagogical educational technologies were developed, and hybridity, interactivity, multiformat, and feedback were identified as the main factors for their success. Pedagogical implications for teaching in higher education are presented.